2022
DOI: 10.1186/s40360-022-00563-9
|View full text |Cite
|
Sign up to set email alerts
|

TCDD exposure alters fecal IgA concentrations in male and female mice

Abstract: Background Activation of the aryl hydrocarbon receptor (AhR) can alter diurnal rhythms including those for innate lymphoid cell numbers, cytokine and hormone levels, and feeding behaviors. Because immune responses and antibody levels are modulated by exposure to AhR agonists, we hypothesized that some of the variation previously reported for the effects of AhR activation on fecal secretory immunoglobulin A (sIgA) levels could be explained by dysregulation of the diurnal sIgA rhythm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In addition, the DCs can secrete BAFF or APRIL to regulate Ig class switching in the B-cell response [35]. Following this, pIgR on the surface of intestinal epithelial cells can bind to IgA and facilitate its transport across the mucosal epithelial barrier and into the lumen of the mucosa [36], which is secreted into the intestinal lumen. In this experiment, the relative expression levels of intestinal mucosal immune-related gene mRNA in the WIV + AMP-ZnONP group were significantly increased compared to the control and WIV groups, suggesting the activation and recruitment of intestinal B cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DCs can secrete BAFF or APRIL to regulate Ig class switching in the B-cell response [35]. Following this, pIgR on the surface of intestinal epithelial cells can bind to IgA and facilitate its transport across the mucosal epithelial barrier and into the lumen of the mucosa [36], which is secreted into the intestinal lumen. In this experiment, the relative expression levels of intestinal mucosal immune-related gene mRNA in the WIV + AMP-ZnONP group were significantly increased compared to the control and WIV groups, suggesting the activation and recruitment of intestinal B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Research focusing on the formation of IgA-secreting cells in the intestine revealed that feeding wildtype C57Bl/6 mice with the AhR ligand TCDD alters fecal IgA concentrations independent of the circadian rhythm ( 199 ). However, the authors did not clarify whether the observed phenotype is mediated by a B cell-intrinsic AhR function or associated with AhR activity in the surrounding cells e.g., IECs.…”
Section: The Role Of Ahr In B Cells Plasma Cells and Iga Productionmentioning
confidence: 99%